Coded Justice: Avery Keene #3 - Abrams, Stacey (New York : Doubleday, 2025)
"Avery Keene is back! The fan-favorite former Supreme Court clerk has finally gone out on her own, securing a prestigious position at a high-end law firm in Washington, D.C., where she is about to earn real money and get her life in order after a tumultuous run working as a clerk on the Supreme Court. With her reputation preceding her, Avery is quickly tasked at her new job with becoming a corporate internal investigator. Her new client is Camasca-a mega-tech firm that's on the forefront of developing a new integrated AI system poised to revolutionize the medical industry, particularly by delivering vastly improved health care to veterans. The AI potential is breathtaking, but some disturbing anomalies have plagued Camasca in early testing-including the mysterious death of a Camasca engineer. Avery and her colleagues, Jared, Ling, and Noah, find themselves on a journey to determine whether the anomalies are mere technical glitches, or something much more concerning. Full of twists, behind-the-scenes financial machinations, and the continued blossoming of Avery and her vibrant cast of friends, Coded Justice finds Stacey Abrams' riveting series to be in full swing"--.
new book 2025 summer.
Keywords: Mystery; Novels; Thriller fiction